Enhancing Inclusion, Diversity, Equity and Accessibility (IDEA) in Open Textbook Publishing: The Development of a Guide - Nikki Andersen (Open Praxis)
While open textbooks offer opportunities to enhance inclusion, diversity, equity, and accessibility (IDEA), it is often seen as an afterthought in open textbook publishing processes. By examining existing literature, this paper dispels myths surrounding open textbooks and IDEA, including that openness does not equal inclusion, access or accessibility. This paper then explores issues of authoring privilege in open textbook publishing, before reviewing the diversity and inclusivity of open textbooks published at a regional Australian university. Using cultural relevance reviews from the Open Textbook Library, common themes emerged concerning IDEA in open textbook publishing. To address these themes, this paper then presents a case study, of how a librarian adapted a framework and created a guide on Enhancing Inclusion, Diversity, Equity, and Accessibility (IDEA) in Open Educational Resources (OER), to develop staff awareness and capability when creating open textbooks. The paper ends by discussing the development of the guide and reviewing the limitations and impact of the guide.